Higher mortality rate in patients hospitalised for acute pulmonary embolism during weekends - Gallerani, Massimo; Imberti, Davide; Ageno, Walter; Dentali, Francesco; Manfredini, Roberto (Thrombosis and Haemostasis, 2011)
The management of acute pulmonary embolism (PE) is often challenging and requires specific medical expertise, diagnostic techniques and therapeutic options that may not be available in all hospitals throughout the entire week. The aim of our study was to evaluate whether or not an association exists between weekday or weekend admission and mortality for patients hospitalised with acute PE. Using routinely collected hospital administrative data, we examined patients discharged with a diagnosis of PE from the hospitals of the Emilia- Romagna Region in Italy (January 1999-December 2009). The risk of inhospital death was calculated for admissions at the weekend and compared to weekday admissions. Of a total of 26,560 PEs, 6,788 (25.6%) had been admitted during weekends. PE admissions were most frequent on Mondays (15.8%) and less frequent on Saturdays and Sun- days/holidays (12.8%) (p<0.001). Weekend admissions were associated with significantly higher rates of in-hospital mortality than weekday admissions (28% vs. 24.8%) (p<0.001). The risk of weekend admission and in-hospital mortality was higher after adjusting for sender, hospital characteristics, and the Charlson co-morbidity index. In conclusion, hospitalisation for PE on weekends seems to be associated with a significantly higher mortality rate than on weekdays. Further research is needed to investigate the reasons for this observed difference in mortality in order to try and implement future strategies that ensure an adequate level of care throughout the entire week.
Keywords: Pulmonary embolism; mortality; weekend